ANALYSIS OF DETERMINATION OF SALES PRICE AND PROMOTION OF SALES VOLUME AT FONI AGENT TISSUE SURABAYA - Nuryadi (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2022)
This study aims to describe the analysis of the determination of the selling price and promotion of the sales volume at Foni Tissue Agent Surabaya. The data in the form of a sales report in 2019. The company must have a good selling price and promotion to get an increase in sales every month by the company. The method used to collect data is observation, interview and documentation. The results of this study are based on sales data from Foni Tissue Agent Surabaya in 2019, increasing sales every month. Thus it can be concluded that the analysis of selling prices and promotion of sales volume in Foni Tissue Agent Surabaya can be said to be successful. This is evidenced by the increase in sales every month in 2019.